Peran Mediasi Sistem Kerja pada Kepemimpinan dan Budaya Organisasi dalam Implementasi Nilai Berakhlak di BPS - Alifaldo Daffa Darmawan (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research seeks to analyze the implementation of BerAKHLAK (Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative) values within the Statistics Indonesia/Badan Pusat Statistik (BPS), while also investigating its impact on organizational culture via leadership and work system mechanisms. Utilizing Structural Equation Modeling-Partial Least Square (SEM-PLS), this research draws upon secondary data gleaned from "Organizational Culture Survey Results of the Badan Pusat Statistik 2022", covering 34 BPS work units throughout Indonesia. Findings suggest that, although leadership does not directly have a profound effect on people who play a role in the implementation of "BerAKHLAK" organizational culture in BPS, its total effect - including its effects through system mediation - is profoundly significant. Leadership significantly shapes work systems which in turn have profound effects on people. This study emphasizes the significance of effective leadership and an efficient work system in instilling BerAKHLAK values among BPS employees. In conclusion, effective leadership, if supported by a good work system, has a big influence on team member behavior in accordance with the values ​​of AKHLAK Keywords: BerAKHLAK, Organizational Culture, Leadership, Work System, Reward System